“Их Монгол улсын түүхэнд холбогдох хятад хоёр сурвалж бичиг” номын тухай - Н, Төмөр (Journal of International Studies, 2006)
English title: The Book review “Two Chinese manuscript concerning The Great Mongolian Empire's histroy”